The effect of human PBMCs immobilization on their Аβ42 aggregates-dependent proinflammatory state on a cellular model of Alzheimer’s disease - Kot, Kateryna; Kot, Yurii; Kurbanov, Rustam; Andriiash, Hanna; Tigunova, Olena; Blume, Yaroslav; Shulga, Sergiy (Frontiers in Neuroscience, 2024)
The leading pathological mechanisms of Alzheimer's disease (AD) are amyloidosis and inflammation. The presented work was aimed to study the effect of human peripheral blood mononuclear cells (hPBMCs) cells-matrix adhesion on their pro-inflammatory state in vitro. Although direct interaction of Аβ42 to hPBMCs is not a cellular model of AD, PBMCs may serve as test cells to detect Аβ42-dependent molecular effects in monitoring disease progression. PBMCs are used to assess changes in cytokines released in response to diseases or AD-specific cytotoxic molecules such as Aβ42. The effect of rАβ42 on the concentration of endogenous Aβ40 and pro-inflammatory cytokines TNFα and IL-1β in hPBMCs that were cultured in suspension and immobilized in microcarriers for 24 hours were investigated. The localization and accumulation of Aβ40 and rAβ42 in cells, as well as quantitative determination of the concentration of Aβ40, TNFα and IL-1β, was performed by intravital fluorescence imaging. The results were qualitatively similar for both cell models. It was determined that the content of TNFα and Aβ40 in the absence of rAβ42 did not change for 24 hours after incubation, and the content of IL-1β was lower compared to the cells that were not incubated. Incubation of cells in vitro with exogenous rAβ42 led to an increase in the intracellular content of TNFα and Aβ40, and no accumulation of IL-1β in cells was observed. The accumulation of Aβ40 in the cytoplasm was accompanied by the aggregation of rAβ42 on the outer surface of the cell plasma membrane. It was shown that the basic levels of indicators and the intensity of the response of immobilized cells to an exogenous stimulus were significantly greater than those of cells in suspension. To explore whether hPBMCs effects in microcarriers were cell-matrix adhesion mediated, we tested the effect of blocking β1 integrins on proamyloidogenic and proinflammation cellular state. Immobilization within alginate hydrogels after incubation with the β1 integrins blocking antibodies showed a remarkable inhibition of TNFα and Aβ40 accumulation in rAβ42-treated cells. It can be concluded that activation of signal transduction and synthesizing activity of a portion of hPBMCs is possible in the presence of cell-matrix adhesion.